Preparation of a Porous polymer by a catalyst‐free diels‐alder reaction and its structural modification by post‐reaction. Issue 17 (5th June 2013) - Kim, Hyungwoo; Choi, Taejin; Cha, Min Chul; Chang, Ji Young
ABSTRACT A microporous polymer is prepared by a catalyst‐free Diels–Alder reaction. A cyclopentadiene with both a diene and a dienophile functionality and a dienophilic maleimide are used for the Diels–Alder reaction. 1, 3, 5‐Tris(bromomethyl)‐2, 4, 6‐trimethylbenzene is reacted with sodium cyclopentadienide to produce the multicyclopentadiene‐functionalized monomer. A crosslinked polymer (CDAP) is obtained by the reaction of the cyclopentadiene monomer with N, N′‐1, 4‐phenylenedimaleimide. The thermal dissociation of the cyclopentadiene dimeric unit and the subsequent Diels–Alder reaction with the maleimide group are investigated by the model reaction. We are able to restructure the crosslinked polymer network by taking advantage of the thermal reversibility of the Diels–Alder linkage. After the post thermal treatment, the BET surface area of the polymer (CDAP‐T) is greatly increased from 317 to 1038 m2 g−1. CDAP‐T is functionalized with pyrene by bromination with N‐bromosuccinimide and the subsequent substitution reaction with aminopyrene. The adsorption property of the pyrene‐functionalized polymer for an aromatic dye is investigated using malachite green. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3646–3653